Digital Anxiety and the Search for Meaning: Integrating Fiqh Principles as a Coping Mechanism for Gen Z’s FoMO - Ilma Ainun Nazila; Siti Nur Ramadhania; Musammil Lateh (Al-Qalam Institute, 2026)
This study aims to explore the influence of Fear of Missing Out (FoMO) on the search for meaning in life and spirituality among Generation Z, as well as its relationship with anxiety and depression levels. Generation Z is known for its high level of digital connectivity, but it also faces significant challenges to its mental and spiritual well-being. This study uses a phenomenological approach and in-depth interviews to explore participants’ subjective experiences. The findings suggest that FoMO is closely related to anxiety, depression, and emotional dissatisfaction arising from excessive social media consumption. Additionally, many Gen Z individuals seek spiritual fulfillment through non-institutional practices such as mindfulness and meditation rather than traditional religious practices. These practices are often considered to be more effective in coping with emotional distress compared to prayer or religious rituals. This research contributes to understanding how Generation Z balances the digital world and their spiritual needs. It is recommended that scholars and policymakers integrate secular practices with Islamic spiritual principles, such as the concept of Fiqh (Islamic jurisprudence), to support the psychological and spiritual well-being of Gen Z. Islamic teachings emphasize balance, discipline, and mindfulness, which can provide a comprehensive framework for addressing the mental and spiritual challenges faced by young people today. The potential role of Fiqh in guiding Gen Z’s spiritual practices offers a balanced approach, combining modern coping strategies with traditional religious wisdom to foster resilience and mental well-being.